Pelatihan Penjadwalan Proyek Konstruksi menggunakan Software Microsoft Project bagi Tenaga Teknik pada CV. Maltitah Indah - Suriati Abd. Muin; Rizki Ayu Saraswati; Sattar, Sattar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Construction projects require good planning, implementation and control to run according to what is expected, including projects that will be carried out by engineers on CV. Maltitah Indah is a service provider company engaged in the general contractor or project implementer located in the city of Makassar, South Sulawesi Province. The purpose of this community service program is to provide education and hands-on practice in the form of training in the form of construction project scheduling training using the Microsoft Project application which aims to improve the quality and soft skills of the workforce, especially engineering personnel, to make project scheduling more practical and can prevent project delays. The implementation method starts from the preparation stage, training stage and evaluation stage to determine the level of understanding, response, and assessment of the success rate of the implementation of the activity. The results of the implementation of this training can increase the understanding of participants who initially did not know how to make project scheduling using the Microsoft Project application and after the training seen from the total number of all participants after the training (post-test), namely, as many as 83.33% understood how to use it and the benefits of the software while as many as 16.67% of participants understood the use of software but were not able to elaborate on the benefits obtained.